Agile Retrospectives a practical guide for catalyzing team learning and improvement - Derby, Esther; Larsen, Diana; Horowitz, David (The Pragmatic Bookshelf, 2024)
In an uncertain and complex world, learning is more important than ever before. In fact, it can be a competitive advantage. Teams and organizations that learn rapidly deliver greater customer value faster and more reliably. Furthermore, those teams are more engaged, more productive, and more satisfied. The most effective way to enable teams to learn is by holding regular retrospectives. Unfortunately, many teams only get shallow results from their retrospectives. This book is filled with practical advice, techniques, and real-life examples that will take retrospectives to the next level--whether your team is co-located, hybrid, or remote. This book will help team leads, scrum masters, and coaches engage their teams to learn, improve, and deliver greater results. For nearly two decades, scrum masters, team leads, and coaches have relied on the first edition of Agile Retrospectivesas an essential resource to facilitate better retrospectives. This edition builds on recent research, reflects the authors' experiences over two decades, and shares wisdom gleaned from the global retrospective community. Find practical advice to level up retrospective skills. Address the challenges of remote and hybrid retrospectives head on. Take advantage of expanded guidance on designing and facilitating retrospectives--based on the questions and concerns of practitioners worldwide. Gain insight into choosing a broad or narrow focus for retrospectives. Explore how to use both objective and subjective data to enable more effective conversations. Learn how to make decisions that stick. Understand the importance of psychological safety and how to foster it in retrospectives. Elevate issues and engage managers in systemic change. Learn from many real-life stories that demonstrate how our advice has impacted retrospectives at organizations around the globe. Finally, find a set of recommended flows that reveal the authors' thought process in designing retrospectives for scenarios teams faced in real life.
Keywords: Teams in the workplace; Project management; Computer software -- Development; Équipes de travail; Gestion de projet